Development of small molecules targeting the pseudokinase Her3 - Lim, Sang Min; Xie, Ting; Westover, Kenneth D.; Ficarro, Scott B.; Tae, Hyun Seop; Gurbani, Deepak; Sim, Taebo; Marto, Jarrod A.; Jänne, Pasi A.; Crews, Craig M.; Gray, Nathanael S. (Bioorganic & medicinal chemistry letters, 2015)
[Display omitted] Her3 is a member of the human epidermal growth factor receptor (EGFR) tyrosine kinase family, and it is often either overexpressed or deregulated in many types of human cancer. Her3 has not been the subject of small-molecule inhibitor development because it is a pseudokinase and does not possess appreciable kinase activity. We recently reported on the development of the first selective irreversible Her3 ligand (TX1-85-1) that forms a covalent bond with cysteine 721 which is unique to Her3 among all kinases. We also developed a bi-functional compound (TX2-121-1) containing a hydrophobic adamantane moiety and the same warhead of TX1-85-1 that is capable of inhibiting Her3-dependent signaling and growth. Here we report on the structure-based medicinal chemistry effort that resulted in the discovery of these two compounds.